Occupational biomechanical risk factors for surgically treated ulnar nerve entrapment in a prospective study of male construction workers - Jennie A Jackson; David Olsson; Laura Punnett; Alex Burdorf; Bengt Järvholm; Jens Wahlström (Nordic Association of Occupational Safety and Health (NOROSH), 2019)
OBJECTIVES: The aim of this study was to determine the association between occupational biomechanical exposures and occurrence of surgically treated ulnar nerve entrapment (UNE). METHODS: A cohort of 229 689 male construction workers who participated in a national occupational health surveillance program (1971-1993) were examined prospectively over a 13-year case ascertainment period (2001-2013) for surgically treated UNE. Job title (construction trade), smoking status, height, weight and age were recorded on examination. Job titles were merged into occupational groups of workers performing similar work tasks and having similar training. Occupational biomechanical exposure estimates were assigned to each occupational group with a job exposure matrix (JEM) developed for the study. Negative binomial models were used to assess the relative risks for each biomechanical exposure and the sums of highly correlated biomechanical exposures. Surgical treatment of UNE was determined via a linkage with the Swedish Hospital Outpatient Surgery Register. RESULTS: There were 555 cases of surgically treated UNE within the cohort. Workers exposed to forceful hand-grip factors had a 1.4-fold higher relative risk (95% CI 1.18-1.63) of undergoing surgical treatment for UNE compared to unexposed workers. Occupational groups comprising workers exposed to forceful hand-grip work showed the highest risks for UNE and included concrete workers, floor layers, ground preparatory workers, rock blasters, and sheet-metal workers. CONCLUSION: Forceful hand-grip work increases the risk for surgically treated ulnar nerve entrapment.